Perceptions of democracy and citizenship between labor organizations with and without collective bargaining agreements - Mangada, Ladylyn L. (1997)
This is qualitative study which attempted to examine the unionized Leyte-Samar workers' political culture. The primary instrument that was used in the study was informal interview with key informants with labor unions with and without collective bargaining agreements. Findings indicated that (a) both types of labor groups share a progressive understanding on citizenship and democracy, (b) freedom of expression, makiamyaw, makiangbition, tuptup and masinugut-non are inherent strengths of the Waray culture which may serve as foundations for democratization of social life and, (c) namamangka sa dalawang ilog, naglilinurulugaring and Waray's malipayon nature are attitudinal barriers in promoting and strengthening democracy.